วิธีเรกูลาร์ไรเซชันสำหรับการประมาณค่าพารามิเตอร์ของโครงสร้างจากผลตอบสนองเชิงโหมดที่ได้จากการวัด - สุวิทย์ วัชรธัญญากร (จุฬาลงกรณ์มหาวิทยาลัย, 2002)
This research addresses the problems of non-uniqueness and sensitivity of solutions to structural parameter estimation from using incomplete and noisy measured modal response. The regularization method is employed by introducing a regularization function to the initial objective function that is cast as the least-squares minimization of the output errors. The regularization function is defined as the Euclidean norm of the difference between the values of the parameters being estimated and the a priori known baseline parameters. The effect of the regularization function on the parameter estimation problem is determined by a regularization factor. Based on a singular value decomposition of the sensitivity matrix of the structural response, it is shown that the optimal regularization factor is obtained by using the maximum singular value of the sensitivity matrix. This condition exists when the effect of the baseline parameters on the parameter estimation problem is minimal. The performance of the proposed parameter estimation algorithm is tested in a numerical simulation study by using a nine-story and a twelve-story shear buildings as the model problems. From the results of the study, it is concluded that for the case of complete measurements, the sensitivity to the measurement noise of the solutions obtained from the proposed algorithm is reduced. The algorithm also performs well for the case of incomplete measurements. In addition, the problem of non-uniqueness is alleviated as evident from the decreasing value of the standard deviation of the parameter estimates. However, the performance of the proposed algorithm tends to decrease as the number of measurement locations decreases.